14-3-3: Defense and regulatory proteins coding by Eucalyptus genome - Furtado, Edson Luiz [UNESP]; Rosa, Daniel Bias [UNESP]; Zamprogno, Karina Carnielli [UNESP]; Marino, Celso Luis [UNESP]; Wilcken, Carlos Frederico [UNESP]; Velini, Edivaldo Domingues [UNESP]; Mori, Edson Seizo [UNESP]; Guerrini, Iraê Amaral [UNESP] (Ipef-inst Pesquisas Estudos Florestais, 2007)
The data mining of Eucalyptus ESTs genome finds four clusters (EGCEST2257E11.g, EGBGRT3213F11.g, and EGCCFB1223H11.g) from highly conservative 14-3-3 protein family which modulates a wide variety of cellular processes. Multiple alignments were built from twenty four sequences of 14-3-3 proteins searched into the GenBank databases and into the four pools of Eucalyptus genome programs. The alignment has shown two regions highly conservative on the sequences corresponding to the motifs of protein phosphorylation and nine highly conservative regions on the sequence corresponding to the linkage regions of alpha helices structure based on three dimensional of dimer functional structure. The differences of amino acid into the structural and functional domains of 14-3-3 plant protein were identified and can explain the functional diversity of different isoforms. The phylogenic protein trees were built by the maximum parsimony and neighborjoining procedures of Clustal X alignments and PAUP software for phylogenic analysis.
Keywords: stress; resistance protein; phylogenic proteins